Seeking the Passionate Career: First‐in‐Family Enabling Students and the Idea of the Australian University. (1st August 2016) - May, Josephine; Delahunty, Janine; O'Shea, Sarah; Stone, Cathy
Abstract: This paper examines the idea of the university from the first‐in‐family enabling students' perspective. It provides an overview of the current crisis of meaning in scholarly commentary that points to a spectrum of meanings about the university. This spectrum ranges from the ancient imaginary of the monastic university as 'ivory tower' to the instrumental idea of the entrepreneurial university. The analysis then reports on the idea of the university in over 40 interviews and surveys of first‐in‐family enabling students who attended two large regional Australian universities in 2014. Their metaphorical understandings of the university constitute a powerful imaginary about what a university is and can do for individuals and the wider society. For many, the resolution of the individualistic passion for knowledge of 'ivory tower' studies and the commitment to the social and economic usefulness of the fully engaged entrepreneurial university can be found in the pursuit of the passionate career.